Vegetasi Tumbuhan pada Kawasan Tepi Hutan Taman Nasional Gunung Gede Pangrango yang Berbatasan dengan Kebun Raya Cibodas - Musyarofah Zuhri; Zaenal Mutaqien; Dian R Nurdiana; Destri Destri; Nudin Nudin; Djuanda Djuanda (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2018)
Cibodas Botanic Garden area is adjacent with natural forest of Mt. Gede Pangrango National Park which consequences both vegetation in the border area are influence each other. The aims of this research were to study plant vegetation of forest area adjacent to Cibodas Botanical Garden and compare it with forest interior using transect method. The results showed that species richness in forest interior were higher than adjacent forest area. Furthermore, number of tree species, basal area and Shannon-Wienner diversity index in forest boundaries were higher rather than forest interior. Habitats along the forest edge were inhabited by trees with large dbh and low tree density. While trees inhibited forest interior areas with high density but small in size. The trees in forest interior were dominated by Schima wallichii, Lithocarpus pallidus and Turpinia sphaerocarpa. While trees in the forest boundary vegetation were dominated by Engelhardtia spicata, Litsea firma and Lithocarpus indutus. The tree age structure of forest interior and forest edge showed an inverted J-pattern and flat pattern respectively. Meanwhile, tree communities on edge forest vegetation showed similar age structure, especially in middle diameter class.